Shifting technology from the universities to a high performance business - Berte, Erica; Neely, Lazarus (Revista de Administração da UFSM, 2009)
The first aim of this study is to identify the external and internal factors that have shaped the performance of Technology-Based Start-up Firms (TBSF) in the US. The second goal is to compare this study with a previous study conducted in Brazil, to identify incubator best practices that may increase the performance of incubated firms. The US study focuses on graduated firms from the Indiana University incubator located in Indianapolis. The main partners of three technology-based start-up firms were interviewed, based on a semi-structured questionnaire. The outcomes from our analysis indicated that the TBSF have both internal and external factors that affect their performance. The analysis showed that as an external factor, the incubator’s connection with university was helpful for obtaining capital. As internal factors, the technical expertise and entrepreneur managerial competence was identified as fundamental factors for TBSF success. The analysis also indicated that some of those factors are different between Brazilian firms and American firms. In Brazil, the management training offered by the incubator is considered very important for the performance of the incubated firms. This was not confirmed in the American study. Knowing what affects the performance of technology-based start-up firms will help incubators offer improved, and more comprehensive services enabling firms to develop and expand.